Conservation tillage: a way to improve yield and soil properties and decrease global warming potential in spring wheat agroecosystems - Sadiq, Mahran; Rahim, Nasir; Tahir, Majid Mahmood; Alasmari, Abdulrahman; Alqahtani, Mesfer M.; Albogami, Abdulaziz; Ghanem, Kholoud Z.; Abdein, Mohamed A.; Ali, Mohammed; Mehmood, Nasir; Yuan, Jianyu; Shaheen, Aqila; et al. (Frontiers in Microbiology, 2024)
greenhouse gas (GHG) emissions are main contributor to climate change; however, croplands are prominent source of GHG emissions. Yet this complex challenge can mitigate through climate smart agricultural practices. Conservation tillage is commonly known to preserve soil and mitigate environmental change by reducing GHG emissions. Nonetheless, there is still paucity of information on the influences of conservation tillage on wheat yield, soil properties and GHG flux particularly on semi-arid Dingxi belt. Hence, in order to fill this gap, different tillage systems (viz. conventional tillage (CT) control, straw incorporation with conventional tillage (CTS), no tillage (NT) and stubble-return with no tillage (NTS) were laid at Dingxi, Gansu province of China under randomized complete block design with three replications to examine their impacts on yield, soil properties and GHG fluxes. Results depicted that different conservative tillage systems CTS, NTS and NT significantly (p < 0.05) increased the plant height, number of spikes per plant, seeds number per meter square, root yield, aboveground biomass yield, thousand-grain weight, grain yield and dry matter yield compared with CT. Moreover, these conservation tillage systems notably improved the soil properties (soil gravimetric water content, water filled pore space, water storage, porosity, aggregates, saturated hydraulic conductivity, organic carbon, light fraction organic carbon, carbon storage, microbial biomass carbon, total nitrogen, available, nitrogen storage, microbial biomass nitrogen, total phosphorous, available phosphorous, total potassium, available potassium, microbial counts, urease, alkaline phosphatase, invertase, cellulase and catalase) whilst decreased the soil temperature and bulk density over CT. However, CTS, NTS and NT had non-significant effect on ECe, pH, and stoichiometric properties (C:N ratio, C:P ratio and N:P ratio). Additionally, conservation based tillage regimes NTS, NT and CTS significantly (p < 0.05) reduced the emission and net global warming potential of greenhouse gases (carbon dioxide, methane and nitrous oxide) by 23.44, 19.57 and 16.54% respectively and decreased the greenhouse gas intensity by 23.20, 29.96 and 18.72% respectively over CT. We conclude that NTS is the best approach to increase yield, soil and water conservation, resilience and mitigation agroecosystems capacity.